Comparison of fluorescent spot test against quantitative enzyme assay for detection of glucose-6-phosphate dehydrogenase deficiency - Halim, Sarah Abdul (2022)
Objectives: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymopathy in the world. Some countries have practiced fluorescent spot test (FST) as a neonatal screening method since the 1980s. However, FST has its own limitations. Quantitative assays such as the careSTARTTM BioSensor1 have been demonstrated to be able to overcome some of these limitations. The objectives of this study are to compare the performance of FST with BioSensor1 in detecting G6PD deficiency in neonates and to verify the reference range of G6PD level for cord blood using BioSensor1. Methods: This study was a cross sectional study involving 455 neonates born in Hospital Universiti Sains Malaysia (Hospital USM), Kelantan, Malaysia beginning June 2020 until December 2020. Two millilitres of cord blood were taken in EDTA bottles to be analysed with BioSensor1 and dried cord blood spots on filter paper were sent for FST to determine the levels of G6PD. Demographics data and birth characteristics were taken from labour room records. Data was recorded and analysed using the Statistical Package for the Social Software (SPSS) version 27. P-value less than 0.05 were considered as significant. Results: The sensitivity of FST was 91% whilst its specificity was 97% at 30% cut-off G6PD activity level. In contrast, at 60% cut-off G6PD activity level, the sensitivity drastically decreased to 29% whilst the specificity was 100%. The overall prevalence of G6PD deficiency was 5.1% and 17.8% for FST and Biosensor1 respectively, demonstrating a drastic difference between the two tests (p < 0.001). The mean G6PD level for term neonates was 6.84 U/gHb whilst for preterm neonates was 6.63 U/gHb. Using independent T-Test, there was no significant difference in the mean G6PD levels between term and preterm neonates. There was also no significant association between different gestational age groups, maternal blood group and birthweight with mean G6PD level when tested using one way ANOVA test. Conclusions: FST has low sensitivity at 60% cut-off G6PD level. This cut-off level reflects intermediate G6PD activity, hence FST missed a significant proportion of G6PD intermediate individuals in our study. At the same time, the prevalence of G6PD deficiency significantly increased with the use of BioSensor1. Gestational age, birthweight and maternal blood group do not have significant association with G6PD level. In a budget constrained facility, it is recommended to use quantitative enzyme assay to screen female neonates and to use FST for male neonates especially in areas where G6PD deficiency is prevalent.